Key Features Defining the Disposition of Bispecific Antibodies and Their Efficacy In Vivo. Issue 1 (February 2020) - Golay, Josée; Regazzi, Mario
Abstract : Abstract: Bispecific antibodies (BsAbs) are novel drugs, with only a few approved for clinical use. BsAbs are versatile molecules that come in many different forms and are designed and produced via genetic engineering. Although BsAbs share several pharmacokinetic (PK) and pharmacodynamic (PD) properties with monoclonal antibodies, they have their own unique characteristics based on their overall structure and specificities. BsAbs are generally more complex to investigate and develop than monoclonal antibodies, because they recognize at least 2 different antigens. Understanding their relative affinities to each target is crucial for determining their mechanism of action and efficacy. Moreover, the presence or absence of an Fc region determines, in part, their in vivo stability, distribution, and half-life. This study summarizes several PK and PD aspects that are specific for BsAbs and are important for the success of these new drugs. We emphasize previous PK/PD studies that have been fundamental for the correct prediction of appropriate dosages and schedules of these new drugs in clinical trials or for defining which drugs may take advantage of individualized and standardized drug monitoring for improved efficacy and safety.